Palladium(ii) complexes of tetradentate donor–acceptor Schiff base ligands: synthesis and spectral, structural, thermal and NLO properties. (20th May 2020) - Celedón, Salvador; Roisnel, Thierry; Artigas, Vania; Fuentealba, Mauricio; Carrillo, David; Ledoux-Rak, Isabelle; Hamon, Jean-René; Manzur, Carolina
Abstract : Structural and NLO behavior of push–pull palladium(ii ) complexes of metallocenyl-containing asymmetric Schiff base ligands. Abstract : This report explores the synthesis and spectral, structural, thermal, electrochemical, linear and nonlinear (NLO) properties of unsymmetrically-substituted N2 O2 tetradentate Schiff base proligand and related bi and trimetallic Pd II complexes. The diprotic proligand Fc-C(O)CHC(4-C6 H4 OH)NH-CH2 CH2 NCH-(2-OH, 4-CO2 H-C6 H3 ) (2, Fc = ferrocenyl = (η 5 -C5 H5 )Fe(η 5 -C5 H4 ))), is synthetized by condensation of the 4-hydroxyphenyl-appended ferrocenylenaminone 1 with 4-formyl-3-hydroxybenzoic acid. The related Pd(ii ) complexes, neutral bimetallic 3 and ionic trimetallic 4, were both prepared via a three-component one-pot template reaction involving the half unit 1, palladium acetate, the CO2 H-functionalized salicylaldehyde and the organometallic salicylaldehyde [Cp*Ru(η 6 -2-OH-C6 H4 CHO)]PF6, respectively (Cp* = η 5 -C5 Me5 ). Compounds 2–4 were isolated as colored air and thermally stable solids in 74–86% yields. They were thoroughly characterized using various physicochemical tools, such as CHN analyses, IR, UV-vis, 1 H and 13 C NMR spectroscopy, TGA and cyclic voltammetry. The molecular structures of 3 and 4 were authenticated by single-crystal X-ray diffraction methods. In both 3 and 4, the four-coordinate palladium atom adopts a square planar geometry with two nitrogen and two oxygen atoms as donors occupying cis positions. Additionally in 4, the ferrocenyl and Cp*Ru + moieties exhibit an anti -conformation with respect to the [Pd(N2 O2 ] Schiff base platform. The electrochemical behavior of the two Pd(ii ) complexes was investigated by cyclic voltammetry, showing in both cases a reversible redox process ascribed to the Fe(ii )/Fe(iii ) couple of the dangling donor ferrocene. Compared to that for 3, the oxidation wave for 4 is anodically shifted by 30 mV, evidencing a greater electron accepting ability of Cp*Ru + vs. –CO2 H. The second-order NLO responses of the push–pull derivatives 2–4 have been determined by harmonic light scattering measurements in N, N -dimethylformamide solutions at 1.91 μm incident wavelength, and rather good quadratic hyperpolarisability β values ranging from 120–160 × 10 −30 esu were determined.